2009
DOI: 10.2174/092986609788490113
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Mechanism of Chaperone Action: Heme Regulation of Hap1 Activity Involves Separate Control of Repression and Activation

Abstract: The Hsp90 and Hsp70 molecular chaperones play important roles in the folding and proper functioning of diverse cellular proteins, including transcriptional regulators and protein kinases. In yeast, several transcriptional regulators and protein kinases are known to be substrates for Hsp90 and Hsp70 molecular chaperones. The yeast heme activator protein Hap1 promotes transcription of many genes in response to heme. It requires Hsp90 and Hsp70 molecular chaperones for its activity to be precisely regulated by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Subsequently, Tissiers et al (1974) observed that exposure of Drosophila to heat shock resulted in the synthesis of a common set of new proteins called "heat shock proteins" (Hsps) or "stress proteins". The heat shock response has been most extensively studied in Drosophila, but a similar response has been observed in cells of a broad spectrum of eukaryotes: Saccharomyces cerevisiae (Lee and Zhang 2009), Dictyostelium (Yamaguchi et al 2005), hamsters (Talorete et al 2008), chickens (Das et al 2009), humans (Morton et al 2009) and also in prokaryotes (Sikora and Grzesiuk 2007;Vigh et al 2007).…”
Section: Heat Shock Responsementioning
confidence: 90%
“…Subsequently, Tissiers et al (1974) observed that exposure of Drosophila to heat shock resulted in the synthesis of a common set of new proteins called "heat shock proteins" (Hsps) or "stress proteins". The heat shock response has been most extensively studied in Drosophila, but a similar response has been observed in cells of a broad spectrum of eukaryotes: Saccharomyces cerevisiae (Lee and Zhang 2009), Dictyostelium (Yamaguchi et al 2005), hamsters (Talorete et al 2008), chickens (Das et al 2009), humans (Morton et al 2009) and also in prokaryotes (Sikora and Grzesiuk 2007;Vigh et al 2007).…”
Section: Heat Shock Responsementioning
confidence: 90%
“…This loss of heme is due, in part, to the activity of Hmx1, in part to less iron availability for insertion into heme, and in part to lower expression levels of heme biosynthetic enzymes (Lesuisse et al 2003). In addition to its role as an enzyme cofactor, heme is also a regulatory molecule that is required for the activation of the transcription factor Hap1 (Guarante 1992;Kwast et al 1998;Lee and Zhang 2009). Hap1 activates the transcription of many genes involved in respiration and aerobic growth.…”
Section: Metabolic Adaptation To Iron Deficiencymentioning
confidence: 99%
“…In the absence of heme (red star), Hap1 is held in an inactive conformation by Ssa proteins (Hsp70) and co-chaperones Ydj1 and Sro9 (orange) that bind to repression modules (RPM). Activation occurs when heme binds to heme-responsive motifs (particularly HRM7), causing association with Hsc82 (Hsp90, green crescent), apparently without dissociation of the repressive chaperones (Lee and Zhang 2009). model. Cytoplasmic Gal3 can sequester Gal80 away from the nuclear compartment in galactose-inducing conditions, suggesting that Gal80 is not bound to Gal4 at the promoter (Peng and Hopper 2000;Peng and Hopper 2002;Pilauri et al 2005).…”
Section: Gal4 Regulation By Intermolecular Ad Maskingmentioning
confidence: 99%
“…In the absence of heme, repressive regions in the central part of Hap1 keep it in an inactive state (Hach et al 1999). In response to heme, a biosynthetic precursor of active cytochromes, repression is relieved and genes in the Hap1 regulon are activated (Lee and Zhang 2009). Heme binds in the central regulatory region of Hap1 (Zhang et al 1998;Hon et al 2000), allowing transcription activation by the C-terminal AD.…”
Section: Hap1 and Mal63 Regulation By Chaperonesmentioning
confidence: 99%